The Representation of Nude Female Figures in Édouard Manet’s Realistic Painting “Olympia” - Azhari, Dhea; Wicaksana, Satria Bagus; Pradhikta, Dyanningrum (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This research aims to dig deeper into women's rights to freedom from ideological constraints. The research method used in this research is descriptive qualitative, by applying Kate Millet's theory of radical feminism. One of Kate Millet's ideas is to support the dismantling of the patriarchal system through social and cultural change, and criticize how culture, literature, and psychology can strengthen and dominate men over women. Observation in the form of extracting core data is obtained from literature studies or relevant previous scientific articles, and secondary data retrieval as a complement to core data comes from websites that have high credibility for information on the artist Edouard Manet, to information on relevant artworks. The results of the research on the representation of nude female figures by Manet in his painting entitled “Olympia” are influenced by several things. The use of art objects in the form of nude female figures has its own meaning for Manet in conveying messages and criticism related to gender issues, especially women. Manet criticizes women's freedom, which is in line with the application of feminism theory in this research. The conclusion of this research is that men tend to exploit women in economic and social terms. Men argue that women do not deserve to be equal to them, because women are objects that must submit to the stronger and dominant. Edouard Manet in painting “Olympia” succeeded in providing social criticism related to feminism through the meaning of the painting which was considered negative by art lovers who saw it.